IMPROVING PERFORMANCE CAPABLE KNOWLEDGE IN YOUTH BASKETBALL BY APPLYING WITH TARGETED SHOOTING PROGRAM - NAGY, Botond Ágoston (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2018)
Today’s basketball player profile can be divided to four resources: physical, mental, spiritual and emotional (Woods, Jordan, 2010). Our research supervised the special basketball demands and the implementations to a training program that could help us to get a correct picture what, when, whom, how, where and why to teach (Winter, 1997). We researched the game performances as the ingredients of competitiveness based on a research of (Baker and Shea, 2013) and the theory of Four Factors by Dean Oliver (2004) as our starting points. Purpose of study. Evaluate of every scientific hypothesis. Observing a special shooting program that is used yearly and simultaneously for a men university basketball team. The main goal of our research is to analyses the common effects of these programs for the game performances of the players. Understanding the basketball player profiles of the participants regarding to their game performances. We’d like to find the details of the improvement of the game performances with a new method that will separate the team and individual parts of the training process. Our hope is that our findings will be useful for planning the basketball practices. We look for the answers which practice topics, drills, tests types and methods are the most effective to increase the special game performance in this model. Methods. We looked for answers on why and how questions with our descriptive research methods. We guaranteed the validity of our work to choose our model systemically. We followed a longitudinal and panel investigation to guarantee the proper tests data. The data were analyzed statistically with ANOVA regression, T probe. We have also used some expert explanation from the gathered data. Hudl video analyzer program. Results. 1. The game statistics of the players who took part on the individual shooting and conditional program do not affect the trend lines of the game performances. 2. The eFG% and FTF do not affect the trend lines of the game performances. No significant different because of the field goal and free throw attempts (434/193 - 88/49 and 99/78 - 39/26). 3. The players who were involved of the morning sessions had more attempts on the games and so higher point/game averages. (49.3 PPG - 14.1 PPG). They executed their shots with a colorful technical repertoire. Their game performance and statistics were more effective. Conclusions. The longitudinal investigation was reasonable because the goals and the programs must be changed within the yearly practice plan. The teaching methods depends on the changes of the offensive strategy of the team. The more information we have about the physical and mental resources, the more effective practice plan can be designed. A competitive shooting program can be properly designed that will consider the significant variants due to our findings. There is a significant connection between the performance of the practice program and the game performances.